Pengaruh diet defisiensi vitamin a terhadap kandungan kalsium dan fosforEmail gigi, penelitian eksperimental pada Tikus (rattus norvegicus)= The Influence of Vitamin A Deficiency Diet on Calcium and Phosphorus .......... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1991)
The aim of the study was to examine the influence of vitamin A deficiency diet during tooth development to calcium and phosphorus content of the enamel. A total 48 male weanling rats (Rattus norvegicus) were randomly grouped into 2 dietary groups. The first group ivas fed with a vitamin A deficiency diet and the other group a normal diet as a control group. Observations of both groups were done at the 6, 8 and 10th week. At the start of experiment, the boundary of the right lower incisor enamel and free gingiva was marked with an ampul saw. After 6th week under ethyl choloride anesthesia, the right lower incisor teeth were cut at the free gingiva and the mark. The same operations were done again after the 8th and 10th week of intervention. The cut teeth were dried at 120Â°C for 30 minutes, after cooling the enamel were separated from the dentin and cementum. The enamel were ashed in muffle furnace at 600Â°C for about six hours, the ashes disolved in 0,1N Ha The calcium content of the ashes were determined by atomic absorption spectrofotometer (AAS) and the phosphorus content were measured by ultra violet-visible spectrofotometer (UV-vis). The resulting data were analized by two way variance analysis and student t-test. The result indicated that vitamin A deficiency diet caused decreasing calcium and phosphorus enamel content (p < 0,001). At 6th week of the intervention the calcium and phosporus enamel content of the two groups did not differ (p> 0,05). At 8th week the calcium and phosphorus enamel content were significantly different among the two groups under comparison (p